2016
DOI: 10.18632/oncotarget.9561
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin on circulating extracellular vesicles as a liquid biopsy to detect breast cancer

Abstract: Extracellular vesicles (EVs) secreted from cancer cells have potential for generating cancer biomarker signatures. Fibronectin (FN) was selected as a biomarker candidate, due to the presence in surface on EVs secreted from human breast cancer cell lines. A subsequent study used two types of enzyme-linked immunosorbent assays (ELISA) to determine the presence of these proteins in plasma samples from disease-free individuals (n=70), patients with BC (n=240), BC patients after surgical resection (n=40), patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 42 publications
4
94
0
Order By: Relevance
“…Fibronectin 1, a fundamental component of the extracellular matrix, is one of the biomarkers of epithelial–mesenchymal transition (EMT), which is an essential step in cancer progression. Serum fibronectin could be a promising biomarker for detecting breast cancer at an early stage 10. Another recent study indicated that fibronectin 1 was upregulated in aggressive TC 11.…”
Section: Introductionmentioning
confidence: 99%
“…Fibronectin 1, a fundamental component of the extracellular matrix, is one of the biomarkers of epithelial–mesenchymal transition (EMT), which is an essential step in cancer progression. Serum fibronectin could be a promising biomarker for detecting breast cancer at an early stage 10. Another recent study indicated that fibronectin 1 was upregulated in aggressive TC 11.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that TGM2 and FN are present in extracellular vesicles derived from cancer cells 15,23 . We therefore isolated EVs using a 200 nM filter cutoff from non-metastatic and metastatic breast cancer cells and conducted nanoparticle tracking analysis and transmission electron microscopy to validate vesicle isolation ( Fig 5A and Supplementary Fig 3A).…”
Section: Transglutaminase-2 Promotes Fibronectin Crosslinking On the mentioning
confidence: 97%
“…Cancer cell‐derived EVs have also been characterized to contain extracellular matrix proteins such as fibronectin, which may mediate interaction between the vesicles and target cells, as well as facilitate anchorage‐independent growth in recipient cells, and promote the induction of pro‐inflammatory cytokines in immune cells . Fibronectin in exosomes has been shown to be an important cargo to promote directional motility and chemotaxis in tumor cells, and the abundance of fibronectin on EVs in the plasma of individuals with breast cancer has indicated its potential as a diagnostic biomarker …”
Section: Functional Cargoes In Microvesicles Derived From Tumor Cellsmentioning
confidence: 99%
“…119 Fibronectin in exosomes has been shown to be an important cargo to promote directional motility and chemotaxis in tumor cells, 120,121 and the abundance of fibronectin on EVs in the plasma of individuals with breast cancer has indicated its potential as a diagnostic biomarker. 122 The chemoattractant potential of EV cargoes provides the potential for invasive cells to deposit cues to facilitate the directed movement of subsequent cells, and the recruitment of other associated cell types such as stromal and endothelial cells. 123 Oncogenic cargo, such as the mutant EGFR variant EGFRvIII can stimulate transformation of naïve cells.…”
Section: Functional Cargoes In Microvesicles Derived From Tumor Cellsmentioning
confidence: 99%